Water Quality Management in Cienfuegos Bay (Cuba) with Integrative Approaches - Losa, Mabel Seisdedo; González, María Elena Castellanos; Carballo, Gustavo Arencibia; Caravaca, Alain Muñoz; Cetina, Jorge Arturo Tello (International Journal of Environment, Agriculture and Biotechnology, 2019)
The aim of this paper is to analyze the contributions of some tools developed with integrative approaches for managing water quality, considering the particular case of Cienfuegos Bay, Cuba. One of the contributions was related to the improvement of a hydrologic monitoring program of this bay with the assimilation of Environmental Totality and Integrated Watershed and Coastal Area Management (IWCAM) approaches. The development of an index for assessing water quality (WQI) of estuarine systems associated with a methodology for implementing a conceptual model on the eutrophication management from systemic and causal approaches, were another developed tools. In addition, a strategic program as a guide for the integrated management of this bay was included considering the participatory and systemic approaches. The assimilation of these integrative approaches for developing scientific tools allowed improving the environmental management at a contextual level and could be generalized in similar aquatic systems